Factores determinantes para la internacionalización de la pyme colombiana por medio de la herramienta del comercio electrónico (2022)
The investigation begins with a look at the behavior of e-commerce, highlighting the high size that SMEs have in Colombia along with their sales in recent years and also promote the incorporation of ICT to increase productivity by contributing to the digital economy. Some strategic allies are exposed in the characterization of the processes in legislative, logistical aspects, means of payment and product display. Among which several tools that can be used for the internationalization of SMEs are mentioned.